Implementasi Sistem Keamanan RFID pada Lingkungan Rukun Warga 015 Tegal Alur Jakarta Barat - Dadang Iskandar Mulyana; Anisah Wulandari; Fahmi Nurul Huda; Reyga Ferdiansyah Putra; Reza Wanandi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Safety is an important aspect of life, especially for communities. The lack of security systems in an environment increases crime rates in areas run by people outside the environment. Therefore, the community service team created an environmental security system by creating a security system using RFID (Radio Frequency Identification) and demonstrated the advantages of this security system compared to traditional systems. The joint concept of community service and research activities uses the results of an interview with the head of his RW 015 Kelurahan Tegal Alur in West Jakarta to identify the desire of residents, especially environmental security members, to develop a security system in the RW area. It will come true. We hope to have a better and simpler security system its usefulness. The outcome of this activity will be implemented to residents of RW 015 Tegal Alur West Jakarta as an example of technology-based environmental facility.